1132 Pediatric Sensory Safe Sleep Study: How to Reduce Sensory Stimulation and Cultivate Compliance Among Children With Special Needs. A New Concept. (27th May 2020) - Rice, B; Albertario, C; Veler, H
Abstract: Introduction: Children with neurodevelopmental disabilities (NDD) frequently suffer from sleep disturbances causing further worsening of behavior, developmental and day-to-day functioning. The important tool used to assess sleep and sleep disorders is polysomnography (PSG). While PSG provides children a less invasive option, children with NDD and/or sensory disorders are often more resistant to this overwhelming and dysregulating procedure. As a result, many children in need of PSG will avoid scheduling a study, or have inconclusive results due to noncompliance. Previous research had shown a program of desensitization improves the number of successfully completed PSGs in NDD children. Our goal is to develop best practice standards to accommodate the individualized need of patients in the sleep lab, in a way that will be available and practical to any center treating NDD children. Methods: Children with NDD require more individualized care tactic therefore, we developed staff education and a process that would help troubleshoot the possibility of patient non-compliance by reducing triggering sensations and unaccommodating technician behaviors. Our process is made up of several key steps to address the behavioral needs of patients: (1) identify patients at risk upon referral; (2) referral to a child life specialist to identify individualized preparation strategies and complete a brief behavioral questionnaire for documentation; (3) mail a preparation kit to the family with a summary of preparation techniques and procedural steps; and (4) ensure sleep technicians have been provided with thorough information to best accommodate the unique patient needs. In addition, PSG conducted with a truncated montage to reduce the number of stimulating sensors applied to the patient and the lab is equipped with sensory toys to provide a relaxing environment. Results: Results will be determined based on comparing the number of successfully completed overnight sleep studies for children with NDD in the years prior to intervention, to the total success rate following the implementation of the intervention process. As a secondary goal, we will gather parent satisfaction scores via morning questionnaires. Conclusion: Research has proven across many modalities that adequate preparation and behavioral modifications produce successful encounters when working with the pediatric population. Support: None